Egalitarian vs. proportional voting in various contexts: An experimental study - Girts Dimdins; Henry Montgomery; Erik Norell (Oñati Socio-Legal Series, 2010)
The paper reports the results of series of experiments aimed at examining people’s readiness to use proportional voting as opposed to traditional, egalitarian ”one person-one vote“ principle. With proportional voting we understand voting procedures where the number of votes per person are determined based on how much the outcome of the vote influences each voter. In one experiment, the participants where asked to vote on a number of issues using various voting procedures. In addition to the traditional ”one issue—one vote“ procedure, the participants were also offered voting schemes that let them freely divide a pre-assigned total number of votes between issues in various ways. The participants were also asked to evaluate the issues to measure their stakes. In another experiment, the participants were asked to evaluate various voting procedures that pre-assigned votes to different voter groups depending on the stakes of these groups. The voting issues were hypothetical scenarios regarding municipal-level decisions about construction work. Participants evaluated proportional voting procedures more favorably when more information was available about the stakes of those involved in the voting process. The overall results show that, at least in experimental conditions, people are ready to use proportional voting and are equally satisfied with proportional and egalitarian voting procedures. However, the question remains open whether proportianal voting schemes can realistically be introduced into real-life democratic process.